Pengaruh Model Pembelajaran Discovery Learning Terhadap Hasil Belajar Siswa - Mutmainnah Mutmainnah; Ma’ruf Ma’ruf; Anisa Anisa (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2025)
The problem in this research is the lack of variation in learning carried out by teachers in the classroom, due to the inappropriate selection of learning models, so that learning is less than optimal. The aim is to evaluate how effective the Discovery Learning learning model is in increasing student understanding compared to conventional learning methods. The method used is an experiment with a quasi-experimental design, namely Nonequivalent Control Group Design. In this study, there were two groups: an experimental group that was taught using Discovery Learning and a control group that was not given this treatment. The population of this study were all 5th grade students at MIN 1 Soppeng. The research hypothesis analyzed using the T test is the statement that the Discovery Learning learning model influences student learning outcomes. The sample in this study was determined by a saturated population, namely 5th grade students consisting of 45 people. The data collection techniques used in this research were multiple choice tests and observation sheets, with pre-tests and post-tests to measure students' cognitive learning outcomes. The instruments used in this research were tests and non-tests. The average pretest score in the experimental class and control class was almost the same, 71.78 and 71 respectively, but in the posttest, the experimental class increased to 88.65, while the control class only reached 77.55. Thus, the experimental class experienced a more significant increase in the average posttest score compared to the control class, indicating that the intervention or treatment applied in the experimental class was more effective in improving student learning outcomes. Hypothesis testing based on t-test analysis shows significant differences between the two groups, where the calculated t value (11.22771) is greater than the t table (2.016692), so the null hypothesis (H_0) is rejected and the alternative hypothesis (H_1) is accepted. These findings show that the Discovery Learning learning model has a greater positive impact on improving student learning outcomes compared to conventional methods, so it can be concluded that this method is effectively used in science learning at MIN 1 Soppeng.